POTENSI KONTRIBUSI RETRIBUSI PENGENDALIAN MENARA TELEKOMUNIKASI TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN LAMONGAN - Adristy, Nadhiva Bayu; Sulistyowati, Endah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2024)
This research research aimed to find out and prove the incline of telecommunication tower control retribution in Lamongan district during 2018-2022. Also, it aimed to find out and prove the potency of telecommunication tower control retribution on Local-owned Source Revenue in the Lamongan district. Moreover, the population was Communication and Informatic Office and Financial Management and Local Asset Board of Lamongan district. The research was descriptive-qualitative. The data were primary and taken throught interviews with 6 informants in the Communication and Informatic Office and Financial Management and Local Asset Board of Lamongan district. Besides primary, the data were secondary and taken through documentation and some reports related to the retribution of telecommunication tower control and Local-owned Source Revenue of Lamongan District. The result showed that the level of contribution of telecommunication tower control on Local-owned Source Revenue during 2018-2022 was very low. However, the Local-owned Source Revenue of Lamongan district during 2018-2022 was increased since sources of revenue had been optimized. In contrast, the Local-owned Source Revenue of Lamongan in 2022 had declined as one of the factors was COVID-19 caused the sources to become less optimized.